On Consensusability of Linear Interconnected Multiagent Systems and Simultaneous Stabilization - Turan, Mustafa Sahin; Xu, Liang; Ferrari-Trecate, Giancarlo (IEEE transactions on control of network systems, 2022)
Consensusability of multiagent systems (MASs) certifies the existence of a distributed controller capable of driving the states of each subsystem to a consensus value. We study the consensusability of linear interconnected MASs (LIMASs), where, as in several real-world applications, subsystems are physically coupled. We show that consensusability is related to the simultaneous stabilizability of multiple LTI systems, and present a novel sufficient condition in form of a linear program for verifying this property. We also derive several necessary and sufficient consensusability conditions for LIMASs in terms of parameters of the subsystem matrices and the eigenvalues of the physical and communication graph Laplacians. The results show that weak physical couplings among subsystems and densely connected physical and communication graphs are favorable for consensusability. Finally, we validate our results through simulations of networks of supercapacitors and dc microgrids.